2021
DOI: 10.3899/jrheum.201551
|View full text |Cite
|
Sign up to set email alerts
|

Persistence to Biologic Therapy Among Patients With Ankylosing Spondylitis: An Observational Study Using the OPAL Dataset

Abstract: Objective To describe the treatment response and persistence to biologic DMARD (bDMARD) therapy in patients with ankylosing spondylitis (AS) in a real-world Australian cohort. Methods This was a retrospective, non-interventional cohort study that extracted data for patients with AS from the Optimising Patient outcomes in Australian rheumatology (OPAL) dataset for the period Aug-2006 to Sep-2019. Patients were classified as either bDMARD initiators if they commenced a bDMARD during the sampling window, or bDMAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…We acknowledged that the KM curves are less reliable at later time-points, in particular for the GOL-treated group (as is reflected in the numbers at risk in Figure 2). 2 As recommended by Pocock et al, 4 we have included the numbers at risk under the KM plots to convey the increasing unreliability of estimates as time from initiation of treatment increases.…”
Section: Dr Griffiths Et Al Replymentioning
confidence: 99%
See 2 more Smart Citations
“…We acknowledged that the KM curves are less reliable at later time-points, in particular for the GOL-treated group (as is reflected in the numbers at risk in Figure 2). 2 As recommended by Pocock et al, 4 we have included the numbers at risk under the KM plots to convey the increasing unreliability of estimates as time from initiation of treatment increases.…”
Section: Dr Griffiths Et Al Replymentioning
confidence: 99%
“…Log-rank tests based on the entire time period (as recom-mended in Pocock at al 4 ) were used to investigate differ-ences between patients receiving different lines of treatment (P < 0.001) and for groups of patients receiving different treat-ments as first-line therapy (P < 0.001). 2 Given the baseline differences in the patients receiving different treatments, we included the results from a Cox proportional hazards analysis (prespecified in the analysis plan) in the article as this allowed adjustment to be made for important baseline confounders. This model again showed significant differences between groups of patients receiving different treatments.…”
Section: Dr Griffiths Et Al Replymentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, there are some important statistical issues relating to time-to-event analysis that have been overlooked by Griffiths et al 1 Addressing these issues will improve the quality of the paper and give readers more faith in the paper's conclusions. Some further questions relating to the analyses presented in Table 3 data have been communicated directly to the corresponding author.…”
mentioning
confidence: 91%
“…Griffiths et al recently reported that in a cohort of Australian patients with ankylosing spondylitis included in the Optimising Patient outcomes in Australian RheumatoLogy (OPAL) dataset, the median persistence (persistence defined as the time to discontinuation of treatment) was longest for patients treated with golimumab (GOL) in all lines of therapy, and shortest for those treated with etanercept (ETN). 1 In drawing this conclusion, the authors have overlooked some statistical aspects relating to the reporting of time-to-event data that make it difficult to evaluate the robustness of their conclusions.…”
mentioning
confidence: 99%